Pelayanan Badan Permusyawaratan Desa (BPD) dalam Persepsi Masyarakat di Desa Ambulu Kecamatan Ambulu Kabupaten Jember - Nur Aini Mayasiana; Ratna Ayu Kartika; Anastasia Murdyastuti (Majalah Ilmiah DIAN ILMU, 2022)
The purpose of this study is to find out how the public's perception of the implementation of the BPD function in Ambulu Village, Ambulu Village, Jember District and to determine the factors that influence community perceptions of the implementation of the BPD function in Ambulu Village, Ambulu Village, Jember District. This type of research is descriptive qualitative research, describing the characteristics of the variables of data collection, reduction, data presentation to drawing conclusions. The results showed that the function of BPD in Ambulu Village, Ambulu District, Jember Regency was not fully maximized. This is because some of the functions that the BPD does not run optimally, including in the activities of discussing and agreeing on Village Drafts and Regulations with the Village Head, almost never involve the community, this is because it is perceived that BPD members are part of the community itself. Then the benefits of the BPD as a reservoir and channel for the voice of the village people are also still not maximized, because not a few people do not understand the function of the BPD as a legal reservoir for the aspirations of the village community. Then the function of the BPD in supervising the performance of the village government, especially the village head, is quite maximal because the BPD is involved in providing the accountability report of the village head during his tenure.